Subject and Object Mutually Transform Each Other: Hermeneutic Diversity of Hegel. - Takahashi, Kazuyuki Ikko (International Journal of Žižek Studies, 2026)
The phrase "to grasp the true not only as substance but also as subject" is a well-known passage in Hegel's Phenomenology of Spirit. S. Žižek has advanced an interpretation to this passage and understood 'substance' as an object (Žižek 1989:210). Žižek has maintained that phenomena should be viewed from a standpoint in which object and subject coincide. This study aims to elucidate the mechanism by which the reconciliation between subject and object is effected. Contrary to Phenomenology of Spirit, in Hegel' s later works, Science of Logic and Encyclopedia, he begins with the concept of the movement of being and explicates a logic through which the subject is generated from that movement. From this logic, nature emerges, and through the mediation of the nature, spirit comes to exist. This entire process can be consistently described as the movement of the subject and the object, which are ultimately unified. Consequently, Žižek's earlier forceful interpretation ultimately converges, at the level of its outcome, with Hegel's theory of unification as articulated in the aftermath of latter's systematic elaboration. Nevertheless, both in Hegel's philosophy and in Žižek's account, the unity of subject and object entails the compelled reconciliation of elements that are, in principle, opposed.